Optimization Of Village Funds With The Development Of Village-Owned Enterprises (BUMDes) Towards An Independent Village In Maryke Plantation Village - Eka Andriani (Jurnal Ekonomi, 2022)
This study aims to determine the optimization of village funds with the development of village-owned enterprises (BUMDes) towards an independent Village in Maryke Plantation Village. This type of research is descriptive qualitative, data collection is done through focus group discussion techniques, in-depth interviews (in-depth interview), observation, and documentation. Data analysis using interactive analysis includes data collection, data reduction, data display, and conclusion. The result of this research is that Maryke Plantation has distributed some ADD to BUMdes. The existence of BUMDes in Maryke village is able to absorb labor. Factors inhibiting the existence of BUMdes in Maryke plantation are budget factors and Human Resources factors. Supporting factors for the existence of BUMDes are government commitment and Natural Resource Potential.